Cumulative live birth rates for women returning to ART treatment for a second ART-conceived child. Issue 6 (8th May 2020) - Paul, Repon C; Fitzgerald, Oisin; Lieberman, Devora; Venetis, Christos; Chambers, Georgina M
Abstract: STUDY QUESTION: What are the success rates for women returning to ART treatment in the hope of having a second ART-conceived child. SUMMARY ANSWER: The cumulative live birth rate (LBR) for women returning to ART treatment was between 50.5% and 88.1% after six cycles depending on whether women commenced with a previously frozen embryo or a new ovarian stimulation cycle and the assumptions made regarding the success rates for women who dropped-out of treatment. WHAT IS KNOWN ALREADY: Previous studies have reported the cumulative LBR for the first ART-conceived child to inform patients about their chances of success. However, most couples plan to have more than one child to complete their family and, for that reason, patients commonly return to ART treatment after the birth of their first ART-conceived child. To our knowledge, there are no published data to facilitate patient counseling and clinical decision-making regarding the success rates for these patients. STUDY DESIGN, SIZE, DURATION: A population-based cohort study with 35 290 women who commenced autologous (using their own oocytes) ART treatment between January 2009 and December 2013 and achieved their first treatment-dependent live birth from treatment performed during this period. These women were then followed up for a further 2 years of treatment to December 2015, providing a minimum of 2 years and a maximum of 7 years of treatment follow-up. PARTICIPANTS/MATERIALS, SETTING, METHODS: Cycle-specific LBR and cumulative LBR were calculated for up to six complete ART cycles (one ovarian stimulation and all associated transfers). Three cumulative LBR were calculated based on the likelihood of success in women who dropped-out of treatment (conservative, optimal and inverse probability-weighted (IPW)). A multivariable logistic regression model was used to predict the chance of returning to ART treatment for a second ART-conceived child, and a discrete time logistic regression model was used to predict the chance of achieving a second ART-conceived child up to a maximum of six complete cycles. The models were adjusted for patient characteristics and previous and current treatment characteristics. MAIN RESULTS AND THE ROLE OF CHANCE: Among the women who had their first ART-conceived live birth, 15 325 (43%) returned to treatment by December 2015. LBRs were consistently better in women who recommenced treatment with a previously frozen embryo, compared to women who underwent a new ovarian stimulation cycle. After six complete cycles, plus any surplus frozen embryos, the cumulative LBR was between 60.9% (95% CI: 60.0–61.8%) (conservative) and 88.1% (95% CI: 86.7–89.5%) (optimal) [IPW 87.2% (95% CI: 86.2–88.2%)] for women who recommenced treatment with a frozen embryo, compared to between 50.5% (95% CI: 49.0–52.0%) and 69.8% (95% CI: 67.5–72.2%) [IPW 68.1% (95% CI: 67.3–68.9%)] for those who underwent a new ovarian stimulation cycle. The adjusted odds of a second ART-conceived live birth decreased for women ≥35 years, who waited at least 3 years before returning to treatment, or who required a higher number of ovarian stimulation cycles or double embryo transfer to achieve their first child. LIMITATIONS, REASONS FOR CAUTION: Our estimates do not fully account for a number of individual prognostic factors, including duration of infertility, BMI and ovarian reserve. WIDER IMPLICATIONS OF THE FINDINGS: This is the first study to report success rates for women returning to ART treatment to have second ART-conceived child. These age-specific success rates can facilitate individualized counseling for the large number of patients hoping to have a second child using ART treatment. STUDY FUNDING/COMPETING INTEREST(S): No funding was received to undertake this study. R. Paul and O. Fitzgerald have nothing to declare. D. Lieberman reports being a fertility specialist and receiving non-financial support from MSD and Merck outside the submitted work. C. Venetis reports being a fertility specialist and receiving personal fees and non-financial support from MSD, personal fees and non-financial support from Merck Serono and Beisins and non-financial support from Ferring outside the submitted work. G.M. Chambers reports being a paid employee of the University of New South Wales, Sydney (UNSW) and Director of the National Perinatal Epidemiology and Statistics Unit (NPESU), UNSW. The Fertility Society of Australia (FSA) contracts UNSW to prepare the Australian and New Zealand Assisted Reproductive Technology Database (ANZARD) annual report series and benchmarking reports. TRIAL REGISTRATION NUMBER: NA.